Synthesis and Study of Some Hydrazone Metal Complexes - Rai, B.K.; Choudhary, Pramod (Asian Journal of Chemistry, 2010)
Co(II), Ni(II) and Cu(II) metal complexes with 3-phenyl quinuoline- 4 (3H)-one-2-carboxaldehyde hydrazone (PQCAH) is synthesized and characterized with the help of elemental analysis. molar conductance, magnetic suceptibility and electronic spectral data. On the basis of experimental data the complexes are found to be octahedral in geometry.